Hydrothermally synthesized nanocrystalline photoactive SnS2 thin films: effect of surface directing agents. (28th January 2022) - Patil, Parag R.; Patil, Satish S.; Dongale, Tukaram D.; Mane, Rahul M.; Patil, Sharad S.; Mali, Sawanta S.; Hong, Chang K.; Bhosale, Popatrao N.; Heo, Jaeyeong; Khot, Kishorkumar V.
Abstract : In the present work, we have synthesized tin disulphide (SnS2 ) thin films via a facile, low cost, single-step hydrothermal route using various surface directing agents. Abstract : In the present work, we have synthesized tin disulphide (SnS2 ) thin films via a facile, low cost, single-step hydrothermal route using various surface directing agents. The SnS2 thin films were characterized for their optical, structural and morphological properties. The optical study illustrated a direct allowed type of optical transition with a bandgap in the range of 1.78 to 2.03 eV. Morphological study demonstrated the formation of hierarchical nutshell surface morphologies, when using different surfactants, having higher surface-to-volume ratios for better light absorption. The structural study revealed that nanocrystalline SnS2 thin films were formed with a pure hexagonal crystal structure with crystallite size ranging between 12.24 and 19.79 nm. Compositional analysis confirmed the formation of pure and stoichiometric SnS2 thin films. Finally, we carefully analyzed the photoresponse properties of the as synthesized and surfactant-assisted SnS2 thin films with the help of a standard two-electrode system on an electrochemical workstation where SnS2 thin films acted as the working electrode and graphite acted as the counter electrode. Photocurrent ( J sc ) was enhanced with the use of the surface directing agents from 0.24 to 0.96 mA cm 2 allied with a photovoltage ( V oc ) from 416 to 610.2 mV. The highest photoelectric conversion efficiency was obtained for the Triton X-100 assisted SnS2 photoanode and it was 0.83%. EIS performance of SnS2 thin films synthesized with surfactants demonstrated reduced charge transfer resistance ( R ct ), which supports the PEC (photoelectrochemical) performance.